Optimizing Green Leadership With N-Soft Sets: A Sustainable Finance Strategy in The Manufacturing Industry in Indonesia - Prasetya, Syarief Gerald; Wardhani, Yustiana; Khoirunisa, Diany (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This research aims to apply the N-soft set algorithm model as one of the Multi-Criteria Data Analysis [MCDA] methods in decision-making related to the analysis of green leadership behavior in the manufacturing industry in Indonesia. Green leadership is considered crucial in reducing the negative environmental impact of manufacturing activities, especially in Indonesia, which in 2022 was recorded as the country with the highest emissions in Southeast Asia and ranked among the top 30 highest[1]emitting countries in the world (IQAir Report). The research sample consists of 30 respondents from various manufacturing companies listed on the Indonesia Stock Exchange. The results indicate that the lack of willingness in the manufacturing industry to implement green finance is driven by two main factors: a lack of leadership support and insufficient financial incentives. Based on these findings, it is recommended to conduct a comprehensive analysis of the Return on Investment (ROI) of green finance practices, integrate these practices into corporate business plans, and provide education and training to company leaders. Additionally, more effective communication on the benefits of green finance is needed, as well as considerations for implementing incentives and rewards, along with utilizing technology and innovation to reduce the costs of implementing green finance practices.